Asymmetric Environmental Effects of Energy-Related Uncertainty: The Role of Renewable Energy - Le, Trung Hai (International Journal of Energy Economics and Policy, 2026)
This study examines the relationship of energy-related uncertainty (EUI) and environmental quality, measured by the per-capita CO2 emissions, using panel data for 27 countries over the period 2000-2023. Employing a CS-ARDL framework, our analysis reveals that EUI exacerbates environmental degradation in the short run but contributes to the reduction of CO2 emissions in the long run. We further incorporate renewable energy penetration as a moderating factor and find that the long-run environmental benefit is conditional on the maturity of a country’s renewable energy sector. In economies with a robust renewable sector, energy-related uncertainty prompts firms and households to shift toward stable and clean domestic energy sources. Causality analysis confirms this interpretation, revealing a unidirectional causal flow from EUI to CO₂ emissions, while finding no link between EUI and other macroeconomic variables. Ultimately, our findings suggest that building a robust, renewable-based energy system is important for creating resilience against the negative environmental impacts of energy-related uncertainty.